Extraction of memory forensic artifacts from windows 7 RAM image - Thomas, Sunu; Sherly, K. K.; Dija, S. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Memory Forensics is a novel and fast growing field in computer forensics, providing access to volatile information unavailable from a disk image. The memory forensics commenced when malware writers began reducing their footprints on the victim's hard disk and instead started storing crucial information within the machine's Random Access Memory. Windows 7 claims to be the most secure version of windows yet, thereby causing the forensic investigations a tedious one. Identification of kernel variables, running processes and extraction of process memory from a Windows 7 memory dump is more difficult when compared with previous versions of Windows. This paper discusses various windows kernel data structures and provides a methodology for extracting the list of running processes from 32-bit and 64-bit Windows 7 memory dump. The paper also presents a method for recovering process memory of running processes from a Windows 7 memory dump.